Exploration du territoire identitaire dans les installations de Fred Wilson - Claudine Armand (Revue LISA)
This article examines Fred Wilson’s plastic approach and attempts to define what is specific about the work of this conceptual Afro-American artist born in New York City in 1954. Ever since his first installations, Fred Wilson has been exploring various spaces of representation, museums, art galleries, and other alternative spaces. He has created in situ works and has always worked in strategic spaces chosen in relation to their social, historical and political context. Selected to represent the United States at the 2003 Venice Biennale, Fred Wilson, like other artists today, questions history, art, and representation. The construction of identity and ethnic relations underlie his heterogeneous, complex, disturbing, and thought-provoking work endowed with political and aesthetic undertones.